Bronze Age tomb from the cemetery of Sasunik - Yengibaryan, Nora (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The Sasunik cemetery is located near the village of Sasunik, in the Aragatsotn province of Armenia. One hundred ninety-four tombs with Bronze and Early Iron Age materials were discovered in the cemetery. This article presents the only Early Bronze Age tomb found in the cemetery of Sasunik.